Effective and enduring surgical treatment for targeted therapy-related paronychia: A retrospective study. Issue 42 (21st October 2022) - Liu, Ting-Hsuan; Wu, Shu-Yu; Tsai, Sheng-Lin; Wu, Chien-Wei; Hou, Chih-Chun; Lai, Chung-Yu; Tzeng, Yuan-Sheng
Abstract : The development of targeted therapy has improved treatment outcomes for patients with non-small cell lung cancer (NSCLC). However, paronychia, a common adverse effect of targeted therapy, remains burdensome. Although conservative treatments for paronychia have been well reported in the literature, studies on the efficacy of surgical partial matricectomy for paronychia, are scarce. This study aimed to evaluate the effect of surgical partial matricectomy in targeted therapy-induced paronychia in patients with NSCLC. This retrospective cohort study included 11 patients with a total of 18 lesions on the big toes. Data on lung cancer stages, types and duration of targeted therapy, onset of paronychia, pain scale scores, conservative treatments, course of matricectomy, paronychia-free interval after matricectomy, and wound condition were collected from medical records. The Wilcoxon signed-rank test was used for analysis. The mean pain scale score after matricectomy was significantly lower than that after conservative treatments (1.00 ± 0.00 vs 2.94 ± 0.87; P < .001) and before treatment (1.00 ± 0.00 vs 3.06 ± 0.80; P < .001). The mean duration of matricectomy was significantly shorter than that of conservative treatments (3.22 ± 1.00 vs 56.56 ± 52.29 weeks; P < .001). Surgical partial matricectomy is an effective and enduring intervention for targeted therapy-related paronychia. It provides a shorter course of treatment, reduced pain, and improved appearance of the healed wound. Furthermore, surgical partial matricectomy could result in a better quality of life during targeted therapy than that of conservative treatments.